ChamerionPopulationData - Unav (Dryad Digital Repository, 2014)
Population information for 134 populations of Chamerion angustifolium sampled across North America, Greenland, Iceland. Includes Lat/Long, Ploidy (Diploid, Mixed-Ploidy, Tetraploid), Information about previous publication, climate data, and PCA axis scores.